Risk analysis of blockchain technology in cross-border e-commerce drug traceability using analytic hierarchy process - Yang, Yuetong; Hawa Hishamuddin; Abdul Hadi Azman (Penerbit Universiti Kebangsaan Malaysia, 2025)
As blockchain technology develops, it is crucial to create a cross-border e-commerce traceability method for imported pharmaceuticals in response to consumer demand for the safety and reliability of medical items. This method promotes the adoption of blockchain technology in the field of traceability as well as the development of a new cross-border e-commerce model for imported pharmaceuticals. However, there are still some technical difficulties and dangers associated with using blockchain in traceability methods. Based on the Analytic Hierarchy Process (AHP), the dangers associated with using blockchain technology for cross-border e-commerce medical traceability were examined in this study. The results show that the difficulty of system integration, the consequences of data breaches, mix-boundary data transfer regulations, market acceptance, and operating costs have the most important impact on the application of blockchain technology in the traceability of pharmaceuticals in cross-border e-commerce within their risk categories.